Pengaruh Guru Pendamping Khusus terhadap Implementasi Pendidikan Inklusif - Chamdani, Muhamad; Wahyudi, Wahyudi; Suryandari, Kartika Chrysti; Rahmadani, Diteana (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
GPK play a key role in the learning process for inclusive education, but some inclusive schools do not yet meet the need for special education teachers. The purpose of this study is to determine the influence of special education teachers on the implementation of inclusive education. This study uses a quantitative correlation method with data collection techniques through questionnaires, observations, and interviews. The population of this study consists of special education teachers in inclusive schools across Kebumen Regency, and the sample was selected using purposive sampling. Data analysis techniques employed Pearson's correlation with the assistance of SPSS. The results of the study indicate that the correlation coefficient at a significance level of 0.01 indicates a strong correlation between special education teachers and the implementation of inclusive education. This strong relationship should be considered to ensure that teachers are evenly distributed across all inclusive schools, enabling education for children with special needs to proceed smoothly and equitably. The conclusion of this study is that GPK have a positive influence on the implementation of inclusive education.GPK dalam proses pembelajaran untuk pendidikan inklusif menjadi bagian yang utama tetapi ada beberapa sekolah inklusi yang belum memenuhi kebutuhan akan guru pendamping khusus. Tujuan penelitian ini yaitu mengetahui pengaruh guru pendamping khusus terhadap implementasi pendidikan inklusif. Penelitian menggunakan metode kuantitatif korelasi dengan teknik pengumpulan data melalui angket, observasi, dan wawancara. Populasi dari penelitian ini yaitu guru pendamping khusus di sekolah inklusi se-Kebupaten Kebumen dan sampel diambil menggunakan purposive sampling. Teknik analisis data menggunakan korelasi pearson dengan bantuan SPSS. Hasil penelitian menunjukkan bahwa hasil korelasi pada signifikasi sebesar 0,01 yang menyatakan bahwa hubungan antara guru pendamping khusus dengan implementasi pendidikan inklusif berkorelasi kuat. Hubungan yang kuat dapat menjadi perhatian untuk meratakan guru di setiap sekolah inklusi sehingga pendidikan bagi anak berkebutuhan khusus dapat berjalan dengan baik dan seimbang. Simpulan penelitian ini yaitu GPK berpengaruh positif terhadap implementasi pendidikan inklusif.